Long- but not short-term estradiol treatment induces renal damage in midlife ovariectomized Long-Evans rats - Zimmerman, Margaret A. (Am J Physiol Renal Physiol, 2017)
Clinical recommendations limit menopausal hormone therapy to a few years, yet the impact of a shorter treatment duration on cardiovascular health is unknown. We hypothesized that both short- and long-term estradiol (E2) treatment exerts positive and lasting effects on blood pressure, vascular reactivity, and renal health. This study was designed to mimic midlife menopause, followed by E2 treatment, that either followed or exceeded the current clinical recommendations. Female Long-Evans retired breeders were ovariectomized (OVX) at 11 mo of age and randomized into three groups: 80-day (80d) vehicle (Veh>Veh), 40-day (40d) E2 + 40d vehicle (E2>Veh), and 80d E2 (E2>E2). In comparison to Veh>Veh, both the E2>Veh and E2>E2 groups had lower systolic blood pressure and enhanced mesenteric relaxation in response to estrogen receptor-α stimulation. Despite the reduced blood pressure, E2>E2 induced renal and cardiac hypertrophy, reduced glomerular filtration, and increased proteinuria. Interestingly, kidneys from E2>Veh rats had significantly fewer tubular casts than both of the other groups. In conclusion, long-term E2 lowered blood pressure but exerted detrimental effects on kidney health in midlife OVX Long-Evans rats, whereas short-term E2 lowered blood pressure and reduced renal damage. These findings highlight that the duration of hormone therapy may be an important factor for renal health in aging postmenopausal women.